Social determinants are associated with clinical presentation of acute pathological fracture in metastatic long-bone disease - Tom M. de Groot; Lotte R. van der Linden; Angad D.S. Bedi; Andreea A. Lucaciu; Caleb C. Jang; Olivier Q. Groot; Job N. Doornberg; Paul C. Jutte; Santiago A. Lozano-Calderon; J.H. Schwab (Journal of Bone Oncology)
Background: Social Determinants of Health (SDOH) are non-medical factors that influence health, which have gained recognition across medical disciplines. Their impact on survival and disease presentation of patients with metastatic bone disease (MBD) remains unexplored. Methods: This retrospective observational study included 712 undergoing surgery for symptomatic long-bone metastases patients between 2013 and 2022. SDOH were evaluated using Cox Proportional hazards regression for post-operative survival. A multivariate logistic regression analysis was performed to identify associated factors for clinical presentation with a completed pathologic fracture. Results: The median overall survival was 264 days (IQR 74–772). Clinical presentation with a pathologic fracture as the initial symptom of metastatic bone disease (MBD) was observed in 15 % of patients (106/712).SDOH factors played a significant role in clinical presentation. Patients with secondary insurance coverage were substantially less likely to present with a pathologic fracture (OR 0.26, 95 % CI 0.14–0.49; p < 0.01). In a sub-analysis of the most common tumors (breast, renal, and lung cancer patients; n = 353), attending college was associated with a significantly lower likelihood of presenting with a pathologic fracture as the initial symptom of metastatic bone disease (OR 0.54, 95 % CI 0.30–0.95; p = 0.03) Conclusion: This study suggests that unfavorable SDOH factors are associated with decreased post-operative survival and a higher likelihood of initial clinical presentation with a completed pathological fracture. Incorporating social determinants into comprehensive care strategies for individuals with MBD may guide targeted interventions and optimize patient management to improve outcomes.